Effect of Ketamine as an Adjuvant to Bupivacaine in Ilioinguinal and Iliohypogastric Nerve Block for Postoperative Analgesia after Inguinal Hernia Repair (Community Based Medical Journal, 2024)
Ilioinguinal and Iliohypogastric nerve block is one of the methods exercised widely to reduce postoperative pain after inguinal hernia repair. Several initiatives are ongoing to prolong the duration of postoperative analgesia by adding various adjuvants to the local anaesthetic agents in different nerve blocks. In this study ketamine has been added as an adjuvant to local anaesthetic bupivacaine in Ilioinguinal and Iliohypogastric nerve blocks. Our study aims to evaluate the effect of adding ketamine to local anaesthetic bupivacaine in ultrasound guided Ilioinguinal and Iliohypogastric nerve block in patient scheduled for inguinal hernia repair under subarachnoid block. This randomized control trial was carried out among 94 patients scheduled for elective inguinal hernia repair under subarachnoid block in Dhaka Medical College Hospital, Dhaka, Bangladesh. Two nerves, Ilioinguinal and Iliohypogastric were blocked by 0.25% bupivacaine under ultrasound guidance after the completion of surgery for postoperative analgesia. The study population was divided equally into two groups having 47 patients in each. Patients of group-A was received 20 ml of 0.25% bupivacaine and 2ml normal saline in the block procedure. Another group, group B patients received 20ml of 0.25% bupivacaine and 1mg/kg of ketamine in the same nerve block. Demographic profiles had no significant differences between two groups (p>0.05). Mean duration of the analgesia or the time of first rescue analgesic requirement were significantly higher in ketamine group (595.24±15.90 minutes) than normal saline group (226.4±20.6 minutes). (p